A Comparative Study on Corrosion Behaviors of Fe35Mn10Cr20Ni35 High‐Entropy Alloy and 304 Stainless Steel in Sulfuric Acid Aqueous Solution. Issue 10 (26th April 2022) - Zhou, Jun; Jiang, Tinghui; Liao, Hengcheng; Chen, Hao; Zhang, Yabo; Zhu, Weijun
Abstract : Herein, the corrosion behaviors of Fe35Mn10Cr20Ni35 high‐entropy alloy (HEA) and commercial 304 stainless steel (304 SS) in 0.5 M H2 SO4 aqueous solutions are evaluated. Potentiodynamic polarization test results indicate that both the prepared HEA and 304 SS possess a large passive interval, illustrating that they have a strong capability to form passive films. The prepared HEA possesses higher corrosion potentials and lower corrosion current densities than that of 304 SS, thus it has more superior corrosion resistance. The electrochemical impedance spectroscopy and electrical equivalent circuits results indicate that the charge‐transfer resistance of HEA is higher than that of 304 SS and the passive films of the prepared HEA is thicker than that of 304 SS. These indicate that the passive film on the prepared HEA has an excellent protective ability to prevent further corrosion. X‐Ray photoelectron spectroscopy results indicate that the passive film of the prepared HEA samples is mainly composed of compacted metal oxides, especially Cr2 O3 ‐dense oxides, while the passive film of 304 SS is mainly composed of loose hydroxides and compacted metal oxides. That is the key reason why the prepared HEA has better corrosion resistance than 304 SS. Abstract : Herein, a novel Fe35Mn10Cr20Ni35 high‐entropy alloy (HEA) is synthesized by arc‐melting. The corrosion behaviors of the prepared HEA and commercial 304 stainless steel (304 SS) are comparatively evaluated using potentiodynamic polarization measurements, electrochemical impedance spectra in 0.5 M H2 SO4 aqueous solutions. The test results indicate that the prepared HEA has more superior corrosion resistance than the commercial 304 SS.